PROBLEMS OF PLANNING PRODUCTION ACTIVITIES OFF LLC TASHKENT COTTON TEXTILE CLUSTER - Hafizov Bunyodjon Zayniddin ogli, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This article discusses the main problems of planning production activities in agricultural clusters, such as depreciation of networks and funds, dependence on suppliers, poor use of innovative technologies and equipment, etc. The analysis of information about the state of the agrocluster and ways to control the effective use of material, financial and information resources is given.